Gender views in the fictions of diasporic Indian English novels - KOMAL KUMARI (International Journal of Multidisciplinary Research and Studies, 2021)
The all-pervasive image of knitting, sewing, quilting, and cooking as a metaphor for the experience and the narrative of diaspora relates it to the imagined feminine role of gathering, recalling, and recording memories and pictures of the past. This is a common image. The burden of remembering home, of recreating those memories within new contexts, and ultimately acting as cultural harbingers of homeland culture continue to fall disproportionately on women, despite the fact that the choice to move from one physical location to another is primarily seen as being one that is made by men, as shown by a great deal of sociological research. However, women continue to be portrayed as being vividly more likely to be the ones who make the move. Reflecting, as it does, the problematics of gendered roles inside an act that remains beyond the agency of women, the issues inherent within this paradoxical scenario are at the centre of modern discourses of the diaspora. The confluence between gender and diaspora, as well as the ways in which the two have influenced one another, has received less attention, despite the fact that diaspora as a historical and current reality has encompassed problems of transnationalism, globalization, hybridity, and multiculturalism.